Assessing the Role of Financial Literacy in Enhancing Personal Financial Decision-Making among Students - Dr. Santanu Kumar Das (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Financial literacy is increasingly recognized on a global scale. The prosperity of an economically thriving society is significantly reliant on financial literacy, as it fosters informed decision-making and promotes economic empowerment. In the context of India’s swiftly changing financial markets, it is essential to evaluate the level of financial awareness among its student mass. As students cultivate long-term financial habits, the significance of financial literacy has become increasingly acknowledged as a crucial competency for effective personal financial management. This research aims to evaluate the influence of financial literacy on enhancing students’ personal financial decision-making. A fundamental grasp of financial principles, including budgeting, saving, investing, and debt management, facilitates efficient money management. Students who possess financial literacy are more likely to make informed choices regarding the allocation of their resources, enabling them to achieve both short-term and long-term objectives. The study highlights the necessity of integrating comprehensive financial literacy programs into university curricula to equip students with essential skills for responsible financial management. Personal financial management is vital for students, as it establishes a foundation for their financial health during their academic pursuits and in the future. The demand for financial literacy education among students is further emphasized by its broader economic advantages, such as enhanced savings rates, reduced debt levels, and improved economic stability. This research also investigates barriers to acquiring financial literacy, including socio-economic challenges, a lack of practical financial experience, and restricted access to financial education resources. Data for this analysis was gathered through a questionnaire administered to 100 respondents using a convenience sampling method to assess how financial literacy contributes to better financial decision-making among students.